Politične razmere na Slovenskem leta 1920 - Perovšek, Jurij (Studia Historica Slovenica, 2021)
The article presents a thorough analysis of the dynamic political situation on Slovene ground in 1920, which was created by protest marches connected to the question of Slovene borders, women’s right to vote, the establishment of the communist Workers’ Socialist Party of Slovenia and the assembly of the catholic Slovene People’s Party (SLS) in Ljubljana. The reality of the communist movement was shown by the railway and general strike in the second half of April 1920, which culminated on April 24, with tragic blood spill on Zaloška cesta in Ljubljana. Politically, the communists were the third strongest actor in the state and for the purpose of their elimination, the Belgrade government passed the so-called Obznana law on December 29, 1920, and forbid their activities. The changing political situation could also be seen at the already limited management of Slovenia. There were several changes of the Land Government for Slovenia, which were connected to the changes of the central government in Belgrade. The year 1920 was a turning point in many ways. It predicted troubled political years ahead and the prediction was right.
Keywords: communist party; constituent assembly; državne meje; elections; Jeglič, Anton Bonaventura; Karađorđević, Aleksandar I; komunistična stranka; Kraljevina Jugoslavija; Krek, Janez Evangelist; Obznana; political history; politična zgodovina; politične razmere; railway and general strike; Slovene borders; Slovene People's party; Slovenija; Slovenska ljudska stranka; stavke; volilna pravica; women's right to vote